Childhood-onset ocular mucous membrane pemphigoid presenting with peripheral ulcerative keratitis: a case report and review of the literature - Eugenia M. Ramos-Dávila; Raul E. Ruiz-Lozano; Alejandro Rodríguez-García; Carlos Álvarez-Guzmán (Journal of Ophthalmic Inflammation and Infection)
Abstract Purpose The purpose of this study was to describe the case of a pediatric patient diagnosed with mucous membrane pemphigoid (MMP) with exclusive ocular involvement presenting at diagnosis with peripheral ulcerative keratitis and provide a review of the literature. Methods A 12-year-old girl presented with cicatricial conjunctivitis and peripheral ulcerative keratitis (PUK). A conjunctival biopsy and direct immunofluorescence revealed linear deposits of IgG, IgM, and C3 at the basement membrane zone, confirming a diagnosis of ocular MMP. Results The patient was initially treated with dapsone 25 mg/day and prednisone 40 mg/day along with topical treatment including cyclosporine 0.05%, loteprednol etabonate 0.05%, and sodium hyaluronate 0.15% and trehalose 3%. Inflammation persisted as an increase in the extension of symblepharon was documented. Subsequently, dapsone was switched to oral methotrexate 15 mg/week and prednisone was successfully tapered to 5 mg/day. After three years of follow-up, disease activity remained quiescent. Conclusions Pediatric mucous membrane pemphigoid with ocular involvement is a rare condition of which few reports have been published, resulting in scarce information regarding its clinical course and response to treatment. We report the first case observed in a Hispanic patient, opening with peripheral ulcerative keratitis, and responding successfully to methotrexate.